TPACK-based blended learning as an implementation of progressivism education: A systematic literature review - Sri Wilda Albeta; L. N. Firdaus; Jimmi Copriady; Masnaini Alimin (ADGVI & Graduate School of Universitas Negeri Yogyakarta, 2023)
Blended learning research has been developed recently. Still, research has yet to examine the rationale for emerging trends and issues regarding TPACK and Blended Learning in terms of educational philosophy. This article focuses on analyzing blended learning based on TPACK (Technological Pedagogical Content Knowledge) from the perspective of the philosophy of progressivism. The educational philosophy of progressivism requires making progress consistently and applying it comprehensively, constructively, and innovatively. In progressivism philosophy, every human being also needs a change to be invariably developed and get improvement. The research method used is qualitative. This research uses library research to explore relevant concepts using various writings on blended learning and TPACK and then analyzed using the progressivism theory. This article explores the results of a literature review on blended learning, TPACK, and progressivism philosophy. A few books and articles published from 2006 to 2021 were searched using Harzing's Publish and Perish through Scopus, Google Books, and Google Scholar databases. The systematic review followed the PRISMA (Preferred Reporting Items for Systematic Review and Meta-Analyses) guidelines. The literature review includes 44 articles and books on blended learning, TPACK, and progressivism philosophy. In this context, a conclusion can be drawn where TPACK-based Blended Learning is an innovation in education following the needs and developments of the times, which is the implementation of the philosophy of progressivism. TPACK-based blended learning results from the philosophy of progressivism, which considers education to be moving in the direction of the times. The philosophy of progressivism requires a fundamental change in the implementation of education towards a better, quality, and real benefit for students.